2013
DOI: 10.1523/jneurosci.3363-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Prominin-1 Allows Prospective Isolation of Neural Stem Cells from the Adult Murine Hippocampus

Abstract: Prominin-1 (CD133) is commonly used to isolate stem and progenitor cells from the developing and adult nervous system and to identifyFinally, despite its expression by various stem and progenitor cells, Prominin-1 turned out to be dispensable for precursor cell proliferation in vitro and in vivo. Nevertheless, a net decrease in hippocampal neurogenesis, by ϳ30% was found in Prominin-1 knock-out mice, suggesting other roles in controlling adult hippocampal neurogenesis. Remarkably, an upregulation of Prominin-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 52 publications
5
66
0
Order By: Relevance
“…The precursor cells in the DG are activated by specific types of spatial learning and by stimuli such as environmental enrichment and physical activity, whereas the SVZ precursor cells are activated by olfactory learning and olfactory enrichment. Consistent with this, one of us (TLW) previously demonstrated that the DG contains a population of latent stem and progenitor cells that can be activated by neural excitation [15][16][17][18] . In contrast, we found that the SVZ precursor cells respond quite differently to this stimulus, with a decrease in neurosphere number in response to depolarizing levels of KCl 17.…”
Section: Representative Resultssupporting
confidence: 54%
“…The precursor cells in the DG are activated by specific types of spatial learning and by stimuli such as environmental enrichment and physical activity, whereas the SVZ precursor cells are activated by olfactory learning and olfactory enrichment. Consistent with this, one of us (TLW) previously demonstrated that the DG contains a population of latent stem and progenitor cells that can be activated by neural excitation [15][16][17][18] . In contrast, we found that the SVZ precursor cells respond quite differently to this stimulus, with a decrease in neurosphere number in response to depolarizing levels of KCl 17.…”
Section: Representative Resultssupporting
confidence: 54%
“…No isoform-specific transcripts were detected in cell #6, but primers recognizing all isoforms produced a signal. Our results also show good concordance with previous studies that revealed the expression of only Prominin1 transcript isoforms 1, 2, and 6 in the subventricular zone (SVZ), and the absence of isoforms 3, 4, 5, and 8 (34,37). We also observed that isoform 1 was expressed exclusively in one of the GFP − cells, while other isoforms were present only in GFP + population.…”
Section: Figuresupporting
confidence: 93%
“…Prom1 expression has been reported in ependymal cells and murine hippocampus [10], [11]. In transgenic Prom1-lacZ mice, Prom1/lacZ was co-expressed with Gfap in cells of the subventricular zone (SVZ) having properties of multi-potent self-renewing neural stem cells.…”
Section: Introductionmentioning
confidence: 99%